2019
DOI: 10.1002/nop2.392
|View full text |Cite
|
Sign up to set email alerts
|

The association of patients' daily summarized self‐rated “real‐time” pain scores with physical recovery after major surgery – A repeated measurement design

Abstract: AimTo determine the associations of patients' documented self‐rated pain with self‐rated early postoperative physical recovery.DesignObservational with repeated measures.MethodsGeneral and orthopaedic inpatients (N = 479) were during the period 2012–2015 screened for pain. Individual daily median pain scores at rest and during activity were based on 4–9 self‐ratings on postoperative days 1 and 2, using the Numeric Rating Scale. Nine items reflecting physical recovery from the “Postoperative Recovery Profile” w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Our study demonstrated that inadequate pain control occurred in 39.49% of the patients after abdominal surgery, which is less than other studies. Wikström et al (2020) revealed that 82% of patients reported ≥4 NRS scores at rest on post-operative day one. Zhang et al (2023) reported that moderate to severe pain was experienced by 58.7% of patients within 24 h following surgery.…”
Section: Status Of Post-operative Inadequate Pain Control In Patients...mentioning
confidence: 99%
“…Our study demonstrated that inadequate pain control occurred in 39.49% of the patients after abdominal surgery, which is less than other studies. Wikström et al (2020) revealed that 82% of patients reported ≥4 NRS scores at rest on post-operative day one. Zhang et al (2023) reported that moderate to severe pain was experienced by 58.7% of patients within 24 h following surgery.…”
Section: Status Of Post-operative Inadequate Pain Control In Patients...mentioning
confidence: 99%
“…Orthopaedic surgery is commonly known to be very painful (Gerbershagen et al., 2014). Poorly controlled postoperative pain has a negative impact on the patient's well‐being and can impede early mobilization, which delays recovery and increases the risk of complications (Dagyaran et al., 2022; Lo et al., 2021; Wikstrom et al., 2020). Opioid analgesics are highly effective in treating moderate to severe pain in the early postoperative phase (Hegmann et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One PROM that has increased in use within nursing research during recent years is the postoperative recovery profle (PRP) by Allvin et al [11]. Te instrument has been used for patients recovering from general and orthopedic surgery [12][13][14][15], heart and lung transplantation [16,17], upper abdominal cancer surgery [18], gastric bypass [19], colorectal cancer surgery [20][21][22], trauma [23], and coronary artery bypass grafting [24]. Te PRP was developed in Sweden, but the instrument has also been translated and used in the United States [25].…”
Section: Introductionmentioning
confidence: 99%